2021
DOI: 10.3171/2021.5.focus21202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of standard neuronavigation and augmented reality on the integrity of the perifocal structures during a neurosurgical approach

Abstract: OBJECTIVE Intracranial minimally invasive procedures imply working in a restricted surgical corridor surrounded by critical structures, such as vessels and cranial nerves. Any damage to them may affect patient outcome. Neuronavigation systems may reduce the risk of such complications. In this study, the authors sought to compare standard neuronavigation (NV) and augmented reality (AR)–guided navigation with respect to the integrity of the perifocal structures during a neurosurgical approach using a novel model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Previous studies have suggested that ARN is suitable for planning trajectories. 13 , 27 ) Observations can be made from the probe's eye view in ARN, allowing the surgeon to confirm the location of the trajectory within the target, as well as the absence of obstructions in the trajectory path ( Fig. 3 ).…”
Section: Augmented Reality In Frame-based Stereotaxymentioning
confidence: 99%
“…Previous studies have suggested that ARN is suitable for planning trajectories. 13 , 27 ) Observations can be made from the probe's eye view in ARN, allowing the surgeon to confirm the location of the trajectory within the target, as well as the absence of obstructions in the trajectory path ( Fig. 3 ).…”
Section: Augmented Reality In Frame-based Stereotaxymentioning
confidence: 99%
“…For the purpose of this study, we used a 140 × 95 × 90 mm custom-made plastic box fixed to the experimental table (initially made for another experimental study [7]). Four metal cross-headed screws were fixed on the top of the box and were solidary to the box, which correspond to the 4 hallmark points (A1, B2, C3, D4) (Fig.…”
Section: Custom-made Modelmentioning
confidence: 99%
“…Errors of precision inherent in the neuronavigation system (referencing or calibration procedures) have already been reported [7,16,27]. This study aims to measure the global error is term of accuracy, or the distance-to-target.…”
Section: Reduction Of Measurement Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the NNS provides permanent intraoperative localization of structures of interest, it has the disadvantage of being expensive and less reliable in posterior fossa surgery [6] . Moreover, using NNS requires the neurosurgeon to shift their focus from surgery to other areas [7] .…”
Section: Introductionmentioning
confidence: 99%